2012
DOI: 10.1007/s00421-012-2514-6
|View full text |Cite
|
Sign up to set email alerts
|

Long-term creatine supplementation improves muscular performance during resistance training in older women

Abstract: This study examined the effects of long-term creatine supplementation combined with resistance training (RT) on the one-repetition maximum (1RM) strength, motor functional performance (e.g., 30-s chair stand, arm curl, and getting up from lying on the floor tests) and body composition (e.g., fat-free mass, muscle mass, and % body fat using DEXA scans) in older women. Eighteen healthy women (64.9 ± 5.0 years) were randomly assigned in a double-blind fashion to either a creatine (CR, N = 9) or placebo (PL, N = 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
62
1
16

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(80 citation statements)
references
References 41 publications
1
62
1
16
Order By: Relevance
“…Örneğin, yaşlılarda kreatin desteği ile kuvvet çalışmalarının kombine edilmesi, kas kütlesi ve gücünü düzeltmiştir. 51 Ancak başka bir raporda da, kreatin desteği kas kütlesi üzerinde, toplam beden kütlesinde veya üst ekstremite gücünde herhangi bir etki göstermemiştir. 52 Bu çelişkili sonuçlar nedeniyle, yaşlılarda sarkopeni tedavisi için kreatin desteği önerilmemektedir.…”
Section: Kreatinunclassified
“…Örneğin, yaşlılarda kreatin desteği ile kuvvet çalışmalarının kombine edilmesi, kas kütlesi ve gücünü düzeltmiştir. 51 Ancak başka bir raporda da, kreatin desteği kas kütlesi üzerinde, toplam beden kütlesinde veya üst ekstremite gücünde herhangi bir etki göstermemiştir. 52 Bu çelişkili sonuçlar nedeniyle, yaşlılarda sarkopeni tedavisi için kreatin desteği önerilmemektedir.…”
Section: Kreatinunclassified
“…The meta-analysis by Devries and Phillips (2014) includes some intervention studies which have been considered by the Panel as pertinent to the claim in this opinion (Bermon et al, 1998;Chrusch et al, 2001;Brose et al, 2003;Carter et al, 2005;Candow et al, 2008;Bemben et al, 2010;Aguiar et al, 2013), but not others (Rogers et al, 2006;Cooke et al, 2014;Gualano et al, 2014). In addition, one of the studies included in the meta-analysis (Neves et al, 2011) was conducted in women with knee osteoarthritis, the results of which cannot be extrapolated to the target population for the claim.…”
Section: Meta-analyses Of Intervention Studiesmentioning
confidence: 99%
“…The Panel notes that three of the studies provided (Chrusch et al, 2001;Rogers et al, 2006;Aguiar et al, 2013) showed an effect of daily consumption of creatine at doses of about 3-6 g for 11-12 weeks in combination with regular resistance training of moderate intensity (three times per week) on muscle strength in adults over the age of 55; that two studies showed an effect of daily consumption of creatine at doses of 5 g for 14 (Brose et al, 2003) and 23 weeks (Gualano et al, 2014), respectively, in combination with resistance training (three times per week and twice per week, respectively) on some measures of muscle strength, but not on others; and that one study (Bermon et al, 1998) did not show an effect of daily consumption of creatine at doses of 5 g for about 7 weeks, in combination with resistance training on muscle strength. The Panel notes that the latter study had shorter duration of the intervention.…”
Section: Human Intervention Studies On the Effect Of Creatine Plus Rementioning
confidence: 99%
See 2 more Smart Citations